The acceptance of panelists for processed carp nuggets - Mukhlishah, Nurul (Anjoro: International Journal of Agriculture and Business, 2022)
Carp is one of the types of freshwater fish that has a high economic value and is easy to cultivate. The people are very familiar with Carp. Carp is one of the types of freshwater fish that is favored by the public because of its delicious meat and is rich in protein. One of the problems when harvesting carp is the high damage to fish due to a lack of understanding of fish quality. Fish processing is one of the ways to prevent fish from rotting. One of the efforts to process fish is to make it into fish nuggets. Nuggets are products that have been heated until they are precooked, and then are frozen. This study aims to determine the acceptability of panelists in processing carp nuggets. This research was conducted from March to April 2022. The manufacturing of carp nuggets was carried out at the Food Technology Laboratory, Faculty of Agriculture, Universitas Indonesia Timur, Makassar. The ingredients that were used in making carp nuggets were carp meat, wheat flour, tapioca flour, salt, garlic, pepper, eggs, water, breadcrumbs, and cooking oil. Based on the results and discussion of the average value of treatment for A1 (100% wheat flour) is 2.8, the average value for treatment for A2 (100% tapioca flour) is 3.3, and the average value of treatment for A3 (50:50) is 3.8 so it can be concluded that the panelists are more accepting of carp nuggets with a treatment of A3 which are 360 grams of carp meat, 45 grams of flour, 45 grams tapioca flour.